Pengaruh Sistem Informasi Manajemen Kepegawaian Terhadap Kinerja Pegawai Di Sekretariat DPRD Kabupaten Ogan Ilir - Muhammad Deni; Aras Tulip; Imam Suroso; Arubina Bangsawan (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
This study aims to determine the effect of personnel management information systems on employee performance at Ogan Ilir Regency DPRD Secretariat. The sample used in this study were 31 respondents of the Secretariat of DPRD Ogan Ilir Regency, the data were obtained through 31 questionnaires. The method used in this sampling was Propotionate Sampling technique. The analytical method was quantitative data analysis using Product Moment Correlation. The results of testing hypothesis showed that the variable: management information systems had a positive effect on employee performance by 0.826. This could be seen from the rtest with 31 respondents with an error rate of 5%. Based on rtabel = 0.367 and rcount = 0.826 where rcount was in the correlation coefficient interval 0.80 - 0.100 stated that the correlation was very strong. Then the rcount was greater than rtable (0.862> 0.367) so that Ha was accepted and Ho was rejected, this indicated a positive and significant relationship between management information systems and employee performance. This relationship had an influence of 68.22% and the remaining of 31.78% was the influence of other factors. From these results, the researcher hopes that the leadership in Ogan Ilir District DPRD Secretariat will implement a personnel management information system so that it can improve employee performance